Efficacy of Eutectic Mixture of Local Anesthetic Cream and Vibrator Device in Pain Reduction during Peripheral Venous Cannulation in a Tertiary Care Center of Central Nepal - Paudel, B.; Acharya, R.; KC, N.; KC, S. (Kathmandu University Medical Journal, 2022)
Background Venous cannulation is a commonly performed procedure which often leads to patient anxiety. Application of a vibrator device and or prior use of topical anesthetics are proven methods to decrease associated pain. Objective To compare the clinical efficacy of prior use of Eutectic Mixture of Local Anesthetic (EMLA) cream and vibrator device in pain reduction during peripheral venous cannulation. Method A true experimental study was conducted in November 2019 among 78 patients aged 20-60 years receiving peripheral cannulation at operation theatre. They were included using consecutive sampling and sorted to interventional and noninterventional group using simple random sampling lottery method. Participants in the non-interventional group received peripheral cannulation using routine technique whereas participants in the interventional group received topical Eutectic Mixture of Local Anesthetic cream or vibrator device prior to cannulation. Perceived post cannulation pain intensity was measured using numerical pain rating scale. Kruskal-Wallis test was used for data comparison. Result The mean age of the participants was 40.57 ± 12.5 years. The median pain score of Eutectic Mixture of Local Anesthetic cream, vibrator and no intervention was 3, 3 and 6 respectively. The reduction in median pain intensity was significantly greater with topical anesthetic cream and vibrator device when compared to the noninterventional group (p < 0.05). Conclusion Prior interventions with Eutectic Mixture of Local Anesthetic or vibrator device are useful in reducing pain intensity during peripheral venous cannulation. Routine use of these in day to day practice could be a part of standard nursing care practice.